2014
DOI: 10.1111/jnc.12822
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor inhibits osmotic swelling of rat retinal glial (Müller) and bipolar cells by inducing glial cytokine release

Abstract: Osmotic swelling of neurons and glial cells contributes to the development of retinal edema and neurodegeneration. We show that nerve growth factor (NGF) inhibits the swelling of glial (M€ uller) and bipolar cells in rat retinal slices induced by barium-containing hypoosmotic solution. NGF also reduced M€ uller and bipolar cell swelling in the post-ischemic retina. On the other hand, NGF prevented the swelling of freshly isolated M€ uller cells, but not of isolated bipolar cells, suggesting that NGF induces a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…We found that, in contrast to ET-1, ET-2 osmotic swelling of bipolar cell somata in retinal slices is an indirect effect, likely mediated by ET-1-induced release of swelling-inhibitory factors from Müller cells. It has been shown that ETs induce a release of growth factors like bFGF from Müller cells [15,31] and that bFGF and TGF-β1 inhibit in part the osmotic swelling of isolated bipolar cells [13]. We found that the inhibitory effect of ET-1 on the osmotic swelling of bipolar cells in retinal slices is abrogated in the presence of inhibitors of the FGF receptor tyrosine kinase and of TGF-β1 superfamily activin receptor-like kinase receptors.…”
Section: Cellular Localization Of Et Receptor Proteinsmentioning
confidence: 86%
See 4 more Smart Citations
“…We found that, in contrast to ET-1, ET-2 osmotic swelling of bipolar cell somata in retinal slices is an indirect effect, likely mediated by ET-1-induced release of swelling-inhibitory factors from Müller cells. It has been shown that ETs induce a release of growth factors like bFGF from Müller cells [15,31] and that bFGF and TGF-β1 inhibit in part the osmotic swelling of isolated bipolar cells [13]. We found that the inhibitory effect of ET-1 on the osmotic swelling of bipolar cells in retinal slices is abrogated in the presence of inhibitors of the FGF receptor tyrosine kinase and of TGF-β1 superfamily activin receptor-like kinase receptors.…”
Section: Cellular Localization Of Et Receptor Proteinsmentioning
confidence: 86%
“…In addition, the outer processes of both cell types display different morphologies, i.e., bipolar cells have a short and thick dendritic tree which contacts the synapses in the outer plexiform layer whereas Müller cells have one relatively thin outer stem process which draws to the outer nuclear layer. In previous experiments, the cellular identity was additionally confirmed by immunohistochemical staining of retinal slices for the Müller cell marker glutamine synthetase and the bipolar cell marker protein kinase Cα [13,42].…”
Section: Animals and Experimental Diabetesmentioning
confidence: 90%
See 3 more Smart Citations